Analysis Of The Impact Of Compensation And Leadership Style On Performance With Motivation As Intervening Variable At PT Adhi Guna Putera - Rizki Ari Wibowo; Syaifuddin; Fenny Krisna Marpaung; Sofiyan (Junal Ilmu Manajemen, 2022)
The purpose of this study was to determine and analyze the effect of compensation and leadership style on work motivation and employee performance at PT Adhi Guna Putera. Where the samples were taken in this study were 103 people. Data were collected using a questionnaire. The data is tested using validity and reliability tests, and the data must meet the elements of the classical assumption test requirements. Test the data analysis using Path Analysis. This study concludes that there is a direct positive and significant effect of compensation and leadership style on employee motivation and employee performance. However, research shows that compensation and leadership style have an indirect and insignificant effect on employee performance through work motivation.